O Sistema de Avaliação do Rendimento Escolar do Estado de São Paulo (SARESP) e o ensino da língua materna em uma rede particular - Machado, Karina (2017)
The evaluative act is present in daily actions and cannot be absent from the educational field. In the school institution, it is represented in different dimensions, which must have a dialogue and subsidize reflections on pedagogical practices carried out inside the classrooms. The external evaluation, one kind of school assessment, has been a guiding instrument in the quality of education for the national State extent and it is this kind that directs the path taken in this research. Specifically in São Paulo State, in order to verify the performance of elementary, middle and high school students, the SARESP - a System of Evaluation of Academic Achievement in São Paulo State was established since 1996. This assessment is organized from the curriculum of São Paulo State and it is attended by students enrolled in the State system, in the 2nd , 3rd , 5th , 7th and 9th grade of elementary and middle school and 3rd grade of high school. The SESI system (Social Service for the Industry) participated, this evaluation in the form of adhesion and from the results of the performance from 2nd grade students of elementary school in the Portuguese Language, this research aims to understand the contribution (or not) in the use of the indicators of this external evaluation, that is, how teachers ( from 1st to 5th of elementary school of the above school system ) use these data performance levels in their school planning in which they are inserted . The data indicated a significant descent in the rate of performance of 2nd graders of this school system and performance levels very close between 3rd and 5th graders, which has led us to narrow our investigative gaze in the process of literacy and literate. Based on qualitative methodology, we applied a questionnaire and interviewed a group of teachers from 1st to 5th grade of one of SESI System schools – SP. The purpose of this questionnaire is to characterize the participant teaching group and the complement of the information that was shared during the interviews on evaluation and pedagogical practices in the process of teaching and learning the native language. The interview was intended to acknowledge the understanding on the formative evaluation (notion used by private school system), evaluative practices developed at school and the use of SARESP results in the pedagogical acts. After analysing the documents of São Paulo State that register SARESP editions in the form of reports, we observed that the large-scale assessment estimate basic skills to be developed by students in each school grade, which, combined the results previously cited, indicated the narrowing of the search for the literacy and literate process developed at school. After analysing the interviews, questionnaires, documents that register the teaching concept and the methodology used in the school systems, the teaching materials and the skills estimated by SARESP, we observed the need to review the practices of literacy developed in this particular school system and training actions aimed to teachers, mostly on track of assessment practices and the singularity of literacy and literate. Especially in the context of evaluation, on the basis of the results presented in previous editions of SARESP, the teachers are led to train their students, but, such practice does not change considerably the results and in the process of literacy and literate, we observed that literate overlaps the teaching of writing technics, leaving gaps in this process, which were revealed in the latest edition of the external evaluation.